Հայկական կոտորածների նախապատրաստումը եւ ջիհադի գործադրումը Վանի նահանգում (1914 թ. յուլիս—նոյեմբեր). - Յարութիւնեան, Աւետիս (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Военный министр Османской Турции Энвер, основываясь на свою тесную дружбу с членами партией Дашнакцутюн, до начала войны с Россией, летом и осенью 1914 г. отправил своих эмиссаров сначала в Эрзурум, затем в Ван и Муш, чтобы договориться с армянами, уговорить перейти их на свою сторону и организовать восстание против российских властей в Восточной Армении. Политическая программа Иттихада казалась ультиматумом, от выполнения которого зависел зависело существование армян в Османской Турции․ The Minister of War of Ottoman Turkey, Enver, based on his close friendship with the members of the Armenian Revolutionary Federation party, before the outbreak of the war with Russia, in summer and autumn of 1914 sent his emissaries first to Erzurum, then to Van and Mush in order to reach an agreement with the Armenians, to take them to his side and organize an uprising against the Russian authoritiesin Eastern Armenia. The political program of Ittihad seemed an ultimatum, on the implementation of which the question of the existence of the Armenians in Ottoman Turkey depended.
Keywords: History